PENERAPAN SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENDISTRIBUSIAN TERHADAP PERTANGGUNGJAWABAN DANA DARI DONATUR PADA YAYASAN GIBBON INDONESIA - Jaya, Tri Intan Mutria; Muanas, Muanas (Jurnal Ilmiah Akuntansi Kesatuan, 2014)
People 's awareness towards development progress leads to an increasing number of non profit organizations. As an organization, it differs from any other institution, especially about who actually own it, is it the members, donors, etc. This research will investigate the application of accounting information system on fund acceptance from donors and its distribution to partners as a form of responsibility. The results show that Yayasan Gibbon Indonesia has been effectively using appropriate accounting system to manage the donors ' funds, supported with necessary documents and procedures in allocating thefunds. Keywords Accounting Information System, Acceptance of Funds, Distribution of Funds, Accountability of Funds